User preference on façade of shophouses built between 1900-1945 in Petaling Street, Kuala Lumpur - Toong, Yong Seng (2016)
The research in regards to the user’s preference on façade of shophouses built 1900 – 1945 in Kuala Lumpur Chinatown (KLC). There were four main issues identified in KLC heritage building of old shophouse facades. The issues identified were I) Problem of heritage facade deterioration; II) Problem of heritage facade modification without sympathetic to neighbours; III) Problem of add-on elements to heritage facade and, IV) Problem of permanent and nonpermanent street structures obstruct the shophouses’ facade. In view of the issues mentioned, there is a need to evaluate users’ preference for heritage buildings of old shophouse facades in KLC. KLC referred as a unique heritage and historic site within the modern city of Kuala Lumpur. The old shophouses formed the major built component in those old towns in accordance to city growth morphological study and their facades contribute to the city image. Besides, the heritage buildings of heritage shophouse facades represent tangible (physical old buildings) and intangible (cultures) heritage elements. The objective of this research is to evaluate user’s (owner/s & tenant/s) preference towards heritage buildings of old shophouse façades in KLC as to assist in urban conservation improvement. Site visit conducted and literature reviews were carried out to identify the problem of the old shophouses in KLC. The thesis uses qualitative research design method for source of data. The study was based on a case study carried out in KLC with interview the user’s (owner/s & tenant/s). The interview entails more structured questions, along the line of a formal survey. Interviews conducted would be jotted and some were recorded digitally should it be agreed by the interviewee. The interviews in verbal data form would be transcribed into the text format by the end of the day. The research findings shown that there were 90% of the users having preference on the heritage shopfront facades as compare to 10% of the users prefer the contemporary façade in KLC. The heritage buildings of old shophouse facades preferred by the users due to the complexity of façade elements composition as human perception has reckoned. The study results were expected could effectively to improve existing conservation guidelines within urban settings and generalised. Last but not least, the study will further leading towards the enhancement quality of conservation to protect shophouse facades stock in KLC and avoid social phenomenon of dissonance and gentrification under the term of urbanisation.